Application of modified Bellinger’s method for optimization of the choice of means of transport - Duchaczek, Artur; Skorupka, Dariusz (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
This paper presents an example of the application of modified Bellinger’s method in the process of optimization of means of transport on the basis of forklift trucks in construction products and materials warehouses. The principles of the discussed method have been described and its pros and cons have been evaluated. The results of the decisive variant ranking have been compared with the results of calculations employing the original Bellinger’s method.